Analisis Faktor yang Mempengaruhi Pemilihan Moda KA Lokal dan KA Feeder sebagai Moda Transportasi Lanjutan KA Cepat Whoosh dari/ke Stasiun Padalarang - Raharjo, Teguh; Pakpahan, Hartati Mediyanti; Prasetyo, Teguh Tuhu (Jurnal Teknik Sipil, 2025)
With the provision of feeder mode (Feeder) train, which consists of Feeder Train and Commuter Line Bandung Raya, it will provide several alternatives for passengers who will continue their trip to the center of Bandung City. Under existing conditions, the Feeder Train experienced a significant increase in interest compared to the Commuter Line Bandung so that there is a gap in the probability of Feeder Train passengers with Commuter Line Bandung Raya. This is what makes researchers feel the need to analyze passengers' preferences in choosing the next mode of transportation and get an understanding of what factors influence the choice of transportation and sensitivity to the model. The number of samples from this study amounted to 96 respondents with data analysis methods using logistic regression analysis and binary logit difference analysis. Based on the results of logistic regression analysis, the following difference utility function model is obtained: PFeeder = 1/(1+ e^(-(0.442 + (X1) + 0.122 (X2) + 0.023 (X3) + 0.020 (X4) + (X5))) with PFeeder = Probability of Feeder Train, PCL = Probability of Comline Baraya, X1 = cost, X2 = frequency, X3 = travel time, X4 = headway, X5 = capacity. From the model, a higher probability of choosing Feeder Train is obtained with a probability value of 61% and the probability value of Commuter Line Bandung Raya is 39%. In other words, respondents still tend to choose Feeder Train to be used as a further mode of transportation, with influencing factors based on test results with high significance, namely cost, time and headway. From the results of the sensitivity analysis of the cost, travel time and headway variables, the cost variable is the most sensitive variable if there is a change in value on the attribute compared to the travel time and headway variables.